Meningkatkan Keterampilan Berbicara melalui Model Pembelajaran Role Playing berbantuan Media Audio Visual pada Siswa Sekolah Dasar - Harmelia Tulak; Tadius; Agustina Lebo (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research is classroom action research (PTK). The implementation of this classroom action research is planned to consist of four components, namely: (1) planning (2) implementation (3) observation (4) reflection. Learning activities are carried out using the Role Playing method. The data sources in this research are class teachers and class III students in the first semester of the 2022/2023 academic year with a total of 30 students, 13 boys and 17 girls. This research is based on students' lack of speaking skills which is caused by students' lack of enthusiasm for learning and teachers only using the lecture method in delivering lesson material, and one way to overcome this is by using the Role Playing learning model assisted by audio-visual media. This research consisted of 2 cycles, which consisted of four meetings. Each cycle consists of 4 stages, namely planning, implementing actions, observing and reflecting. The results of this research show that the Role Playing method assisted by audio-visual media can improve the speaking skills of class III students at SDN 5 Tikala. This can be seen from the improvement in students' speaking skills in cycle 1 with an average score of 54 while in cycle II the average score of students was 85